2017
DOI: 10.1111/ens.12253
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing reveals abundant olfactory genes in the antennae of the rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyralidae)

Abstract: The rice leaffolder, Cnaphalocrocis medinalis Guenée, is an important lepidopteran pest of rice in Asia. Insect olfactory proteins, including olfactory receptors (ORs), ionotropic receptors (IRs), odorant‐binding proteins (OBPs), chemosensory proteins (CSPs) and sensory neuron membrane proteins (SNMPs), are responsible for perception of sex pheromones and host plant volatiles, and thus regulate insect behavior. In the present study, transcriptome sequencing was conducted for C. medinalis antennae to identify g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…There was high homology among the known Orco genes (Jones et al 2005;Xiao et al 2009). In comparison with the number of genes identified in this study, 43 ORs and Orco have been identified in Holotrichia oblita Faldermann , and 46 ORs and Orco have been identified in Cnaphalocrocis medinalis Guenee (Liu et al 2017). We believe that we have identified a sufficient number of genes from the transcriptome.…”
Section: Discussionsupporting
confidence: 48%
“…There was high homology among the known Orco genes (Jones et al 2005;Xiao et al 2009). In comparison with the number of genes identified in this study, 43 ORs and Orco have been identified in Holotrichia oblita Faldermann , and 46 ORs and Orco have been identified in Cnaphalocrocis medinalis Guenee (Liu et al 2017). We believe that we have identified a sufficient number of genes from the transcriptome.…”
Section: Discussionsupporting
confidence: 48%
“…The other HrhoORco and HrhoOR11 with approximately equal expression levels between female and male antennae are likely to function in the detection of food source odors. In addition, HrhoOR37 was orthologous to CmedOR32 according to phylogenetic analysis, and the expression levels of these two OR genes were higher in the FA than in the MA (Liu et al, 2017b). Therefore, we speculate that these two orthologous OR genes may play similar roles in odor detection.…”
Section: Discussionmentioning
confidence: 83%
“…The number of identified PintOBPs was equivalent to that from H . armigera (26) [ 11 ], Dendrolimus kikuchii (27) [ 17 ] and Agrotis ipsilon (33) [ 21 ], and it was significantly greater than that from Cnaphalocrocis medinalis (12) [ 12 ], C . punctiferalis (14) [ 13 ], Manduca sexta (18) [ 43 ] and S .…”
Section: Discussionmentioning
confidence: 99%